THE INFLUENCE OF LOCAL SEARCH ENGINE OPTIMIZATION STRATEGIES ON REGISTRATION INTEREST IN SMART EKELENSIA INDONESIA - Kushardanta Susilabudi; Andika Putra Pertama (STMIK Indonesia Banda Aceh, 2026)
This study aims to examine the role of local Search Engine Optimization (SEO) in increasing prospective students’ registration interest at Smart Ekselensia Indonesia. A quantitative approach was employed using a survey method involving 100 respondents selected through purposive sampling. The collected data were analyzed using simple linear regression with the assistance of IBM SPSS Statistics software. The results indicate that local SEO has a positive and statistically significant effect on registration interest. The coefficient of determination (R Square) value of 0.680 shows that 68% of the variation in registration interest can be explained by local SEO, while the remaining 32% is influenced by other factors beyond the scope of this study. These findings confirm that local search-based digital strategies play an important role in increasing prospective students’ interest in the digital era.